L'utilisation du système de santé et des services sociaux non autochtones chez la population autochtone vivant en milieu urbain - Vallée, Kiliane (Université Laval, 2018)
This research focuses on the use of health and social services by the Aboriginal peoples living in urban areas. Studies on the subject show that there are social inequalities in this population, which results, among other things, in a difficulty in accessing these services. The lack of culturally appropriate services and the presence of discrimination among providers are the two main factors raised by the scientific literature about this issue. In a culturalist approach, the cultural peculiarities of First Nations, Métis and Inuit are put forward to explain it. This study offers a different take on the issue by examining the experience of First Nations people in terms of their relationships with professionals in the health and social services. In what ways do they feel perceived by them? What are the impacts of these impressions on their experience and use of services? The results show that First Nations people experience different experiences, ranging from satisfaction to loss of confidence in the services received. However, the negative elements spontaneously raised by the participants are more often organizational than relational. The First Nations people who participated in this thesis are looking for empathic professionals and egalitarian relationships. Ce mémoire s’intéresse à l’utilisation du réseau de la santé et des services sociaux chez la population autochtone vivant en milieu urbain. Les études sur le sujet démontrent qu’il existe des inégalités sociales chez cette population se traduisant, entre autres, par une difficulté d’accès à ces services. Le manque de services culturellement adaptés ainsi que la présence de discrimination chez les prestataires de services de santé et sociaux sont les deux principaux facteurs soulevés dans la littérature scientifique envers cette problématique. Dans un discours culturaliste, les particularités culturelles des Premières Nations, Métis et Inuit sont mises de l’avant pour l’expliquer. Cette étude propose un regard différent sur la question en examinant ...